Radar data acquisition and processing system for UAV positioning applications - Başpınar, Ömer Oğuzhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Small drones have started to be utilized by researchers for applications such as object tracking, imaging and remote sensing as they become more available, inexpen sive and capable with the advancements in sensor and UAV technologies. Drones can be equipped with sensors such as cameras and radars. Radars can be used onboard for navigation aid by detecting range and velocity, as well as for radar imaging applica tions. Although the latter is common, they can be useful in navigation since they are barely affected by weather conditions or smoke. FMCW radars are fitting devices for drones since they are relatively simple and can be lightweight. Therefore, following a broad FMCW radar survey, a custom drone system and a radar system are designed and implemented for UAV positioning applications. A postprocessing algorithm for detecting the altitude above ground level and ground reflection is developed, and a range compensation method is proposed to improve the performance of the algorithm. Results of a field experiment showed that the radar system can be used for air borne positioning applications. Detected altitudes show similarity to the flight video. Reflections coming from the metal objects are distinguished from those coming from the ground. Range compensation method enabled detecting much lower altitudes, and magnitude of ground reflections obtained from different altitudes became similar. The system can be used in landing aid applications with a proper autopilot software and in SAR imaging with a position sensor more accurate than GPS.
Keywords: Drone aircraft -- Control systems.; Radar -- Data processing.